Review: Utilization of Decision Support System in Identification of Drug-related Problems in Geriatric Patients - Larasati, Niken; Sugiyono, Sugiyono; Padmasari, Siwi (Universitas Ahmad Dahlan, 2025)
Background: Globally, there were 703 million people aged 65 years or older in 2019. The largest population were in East and Southeast Asia (260 million) followed by Europe and North America (more than 200 million). This number is expected to grow to over 1.5 billion people by 2050. Treatment-related problems are events associated with drug use that may affect the patient's therapeutic goals. The prevalence of treatment-related problems is estimated to be 45.1% in populations meeting criteria for advanced age, polypharmacy, and multimorbidity. A decision support system (DSS) is developed based on individual conditions to provide recommendations for therapeutic and dosage selection, and to prevent drug interactions in complex cases. This study aims to evaluate the use of DSS in identifying treatment-related problems in geriatric patients across various countries. Method: This study uses a narrative review method to systematically discuss previous research findings. Results: This review examined journals on the use of decision support systems in identifying drug-related problems in geriatric patients. A search article published between 2016-2021 in the PubMed database yielded 10 relevant articles. DSS tools have shown to improve the continuity of care for geriatric patients. Previous DSS tools used include AGAlink, G-MEDSS, PRIMA-eDS, STRIPA, SENATOR, and TRIM. Conclusion: DSS represents a significant technological advancement that can be applied to prevent and reduce inaccuracies in prescribing, particularly for geriatric patients.